Steven Lubet's American dilemma. (8th August 2021) - Forrest, David
ABSTRACT: This essay examines the ideological underpinnings of Steven Lubet's Interrogating Ethnography . I argue that Lubet's text draws from an ideological tradition best exemplified by An American Dilemma, Gunnar Myrdal's influential 1944 study of U.S. race relations. This tradition posits the notion of an enduring and egalitarian American Creed, which ensures that the United States' liberal-democratic institutions are fundamentally decent and fair in principle. I show how an unsubstantiated belief in the American Creed informs Lubet's claims about contemporary ethnographic research and, in doing so, limits the usefulness of his text. Ultimately, I conclude, Interrogating Ethnography epitomizes the ways in which troublesome ideological frameworks continue to shape debates about social science methodology.